Some aspects of early medieval copper-alloy technology, as illustrated by a study of the Anglian cruciform brooch - Mortimer, C; Mortimer, Catherine (1990)
﻿ This thesis aims to examine the modes of production and the sources of metal supply for Migration period bow brooches, concentrating on a single form, the Anglian cruciform brooch. The thesis is in two volumes; text and bibliography (volume 1), catalogues, tables, illustrations (volume 2). The text is in six chapters. Attitudes to artefact studies are briefly discussed in Chapter 1 and the techniques employed in this study are outlined. Chapter 2 places the cruciform brooch forms into a simple hierarchical typology by formal similarity. A relative chronology is gained by contextual evidence, with absolute dates given by associations with other artefact types. Similarities between early English and continental forms are shown to be adequate to suggest importation, during the first half of the fifth century. Frisian and north German brooches have a special place in this system. Parallel stylistic development persisted during the second half of the fifth century but sixth-century English brooches are well distinguished from their continental contemporaries. Simple brooch types are thought to have had a long period of production and use. By examining methods of casting and assembling cruciform brooches, Chapter 3 establishes the types and ranges of technical variation observable. Some of these technical attributes provide links between England, Frisia, northern Germany and Denmark. English brooch manufacture is diverse throughout the period under study. Norwegian metalworkers developped a very different style and the technical evidence suggests a movement towards standardisation and mass production. In Chapter 4 we discover the types of alloy used and discuss the likely sources. Initially the alloys used were leaded brasses or bronzes. By the sixth century, copper alloys were commonly very impure. It is suggested that recycling provided a major part of the raw materials for cast copper alloys. Imports of copper alloys from France or the Celtic regions of Britain are relegated to a position of minor importance. The chemical compositions of Norwegian, Frisian, north German and Dutch cruciform brooches demonstrates access to high-tin, high-purity bronzes prevailed throughout the period. Brasses and mixed alloys were also available, probably originating from scrap. With the exception of Frisia, which appears to be more similar to Kent, alloy supplies were similar throughout the Scandinavian and continental cruciform brooch production. Chapter 5 provides a synthesis for these findings. Plans are given for a project extension into other regions (Chapter 6).